2019
DOI: 10.1097/md.0000000000014587
|View full text |Cite
|
Sign up to set email alerts
|

IL-1 inhibition improves insulin resistance and adipokines in rheumatoid arthritis patients with comorbid type 2 diabetes

Abstract: Recently, it has been shown that some well-known pathogenic mediators in rheumatoid arthritis (RA), such as interleukin-1β (IL-1β) and tumor necrosis factor (TNF), could play a pathogenic role in insulin resistance and (IR) and type 2 diabetes (T2D). In this 6-month longitudinal study, we aimed at investigating if the inhibition of IL-1 or TNF is associated with an improvement of IR in RA patients with comorbid T2D and the possible effects on selected serum adipokines. RA patients with comorbid T2D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 79 publications
0
25
0
2
Order By: Relevance
“…These results showed that the dynamic equilibrium between IL-1-dependent intracellular signaling and IL1R2 was associated with the progression of human diseases. IL-1-dependent intracellular signaling attributes to the pathogenesis of many diseases including arteriosclerosis [8], rheumatoid arthritis [25], type 2 diabetes [25,26], and pustular psoriasis [27]. The inhibition of IL-1, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These results showed that the dynamic equilibrium between IL-1-dependent intracellular signaling and IL1R2 was associated with the progression of human diseases. IL-1-dependent intracellular signaling attributes to the pathogenesis of many diseases including arteriosclerosis [8], rheumatoid arthritis [25], type 2 diabetes [25,26], and pustular psoriasis [27]. The inhibition of IL-1, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…TLR2/4 activation causes a proinflammatory response in autoimmune diseases and contributes to an obesity-induced inflammatory response by increasing TNF-a and IL-6 levels in RA and TNF-a, IL-6, IL-23, and IL-10 levels in SLE [7]. Some inflammatory mediators of the TLR2/4 pathway, including JNK, IL-1, and IL-6, induce IR by impairing insulin receptor substrates and PI3K–AKT pathway activation [34, 36]. Additionally, an increase in free fatty acids, which is observed in IR, decreases the secretion of adiponectin, an anti-inflammatory adipokine that increases the secretion of and sensitivity to insulin.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence rates of DM and AR in those with any disability are more than doubled compared to those without disability [ 4 ]. Furthermore, previous studies reported a high prevalence of AR among individuals with DM and vice versa [ 5 , 6 , 7 , 8 , 9 , 10 ], which has motivated researchers to examine the links between the two diseases [ 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%